2023
DOI: 10.3390/biomedicines11071859
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Supplements Which Upregulate Nitric Oxide on Walking and Quality of Life in Patients with Peripheral Artery Disease: A Meta-Analysis

Abstract: This systematic review pooled evidence from randomised controlled trials (RCTs) on the effectiveness of dietary upregulators of nitric oxide (NO) in improving the walking and quality of life of patients with peripheral artery disease (PAD). RCTs examining the effect of dietary upregulators of NO in patients with PAD were included. The primary outcome was the maximum walking distance. Secondary outcomes were the initial claudication distance, the six-minute walking distance, quality of life, the ankle-brachial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…While there was an overall moderate improvement noted by these authors in claudication onset distance, when assessed across all 4 categories of NO-boosting supplements (i.e., NO donors including nitrate/nitrite, the NO modulators citrulline and/or arginine, NOS inducers, and antioxidants), the only supplement category that significantly improved claudication onset vs. placebo was antioxidants. The large variability in treadmill walk performance in PAD patients in general ( 20 , 44 ) and in our small cohort in particular ( Figure 3 ) coupled with the high antioxidant content of beetroot juice ( 45 ), are factors that likely diminished our ability to detect any potential improvements in walking performance in the present investigation. The large between-patient variability and the high content of antioxidants within both BR nitrate and BR placebo could also explain the lack of nitrate supplementation influence on exercise tolerance during our isolated plantar flexion testing.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…While there was an overall moderate improvement noted by these authors in claudication onset distance, when assessed across all 4 categories of NO-boosting supplements (i.e., NO donors including nitrate/nitrite, the NO modulators citrulline and/or arginine, NOS inducers, and antioxidants), the only supplement category that significantly improved claudication onset vs. placebo was antioxidants. The large variability in treadmill walk performance in PAD patients in general ( 20 , 44 ) and in our small cohort in particular ( Figure 3 ) coupled with the high antioxidant content of beetroot juice ( 45 ), are factors that likely diminished our ability to detect any potential improvements in walking performance in the present investigation. The large between-patient variability and the high content of antioxidants within both BR nitrate and BR placebo could also explain the lack of nitrate supplementation influence on exercise tolerance during our isolated plantar flexion testing.…”
Section: Discussionmentioning
confidence: 81%
“…However, two additional supplementation studies, one using BR nitrate acutely ( 28 ) (70 mL Beet-IT) and one that administered sodium nitrite tablets for 3 months ( 43 ) reported no significant improvements in walk distances relative to placebo. When examined collectively in a recent meta-analysis of studies investigating dietary nitrate and other upregulators of NO in PAD ( 44 ), it was reported that the improvements in maximum walk distance/duration did not achieve statistical significance. While there was an overall moderate improvement noted by these authors in claudication onset distance, when assessed across all 4 categories of NO-boosting supplements (i.e., NO donors including nitrate/nitrite, the NO modulators citrulline and/or arginine, NOS inducers, and antioxidants), the only supplement category that significantly improved claudication onset vs. placebo was antioxidants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations